2011
DOI: 10.1108/09564231111155079
|View full text |Cite
|
Sign up to set email alerts
|

Crowd‐funding: transforming customers into investors through innovative service platforms

Abstract: Purpose -The purpose of this paper is to analyze the emerging crowd-funding phenomenon, that is a collective effort by consumers who network and pool their money together, usually via the internet, in order to invest in and support efforts initiated by other people or organizations. Successful service businesses that organize crowd-funding and act as intermediaries are emerging, attesting to the viability of this means of attracting investment. Design/methodology/approach -The research employs a "grounded theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
565
0
43

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 859 publications
(671 citation statements)
references
References 60 publications
19
565
0
43
Order By: Relevance
“…Online crowdfunding, defined as "a collective effort by individuals who network and pool their money together, usually via the Internet, to invest in or support the efforts of others" (Ordanini et al 2010), has received a great deal of attention from entrepreneurs and policymakers as a promising avenue to fostering entrepreneurship and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Online crowdfunding, defined as "a collective effort by individuals who network and pool their money together, usually via the Internet, to invest in or support the efforts of others" (Ordanini et al 2010), has received a great deal of attention from entrepreneurs and policymakers as a promising avenue to fostering entrepreneurship and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…However, several analyses show the signifi cant role of social media in project success (e.g. Mollick 2014;Ordanini et al 2011;and Giudici et al 2013). Second, instead of using the number of rewards, the quality of rewards could be included.…”
Section: Results Limitationsmentioning
confidence: 99%
“…Bellefl amme et al 2014 used Kleeman et al 's defi nition (2008) of crowdsourcing and extended it to defi ne crowdfunding as a "an open call, essentially through the internet, for the provision of fi nancial resources either in form of a donation or in exchange for some form of reward and / or voting rights, in order to support initiatives for specifi c purposes" (Bellefl amme et al 2014, 588). Ordanini et al (2011) considered the internet to be a key element of crowdfunding. Joenssen et al (2014), however, argued that the basis of crowdfunding is not determined by the launch of crowdfunding campaigns on the internet and suggested that crowdfunding is "a process where commercial or non-commercial projects are initiated in a public announcement by organizations or individuals to receive funding, assess the market potential, and build customer relationships.…”
Section: The State Of the Artmentioning
confidence: 99%
“…Social media analytics is an act of collecting and interpreting the data posted on social media in order to conduct market research, learn about a target audience, collect feedback that drives strategic business decisions, etc [3]. With the growing number of population on social media, it's important to know what people talk about media whether it's for business, scientific or sociological reasons.…”
Section: What Is Social Media Analytics?mentioning
confidence: 99%